Improved algorithm based on result zone for GNSS attitude measurement - jie LIShi; an LIZhi; lei PANGChun; lin YUYong; Yong WANG (Tongxin xuebao)
The correlation of search zone was not included in the result zone algorithm for GNSS attitude measurement, which led to extended time for initialization and oversize range for searching, then an improved algorithm in which search zone was bounded by ambiguity was proposed in the following procedures. First, search space for ambiguity with the condition of fixed baseline length was deduced. Then combination of two dimensional search zone was established by the smaller two search spaces and their relations with heading and elevation angle. Finally the integer ambiguity was de-fined on the basis of result zone search with the mini l two-order residuals of baseline. The experiment reveals that the correlative information on search zone is fully exploited and the size of search space is reduced, with time for initializa-tion reduced to less than 40 seconds.